2020
DOI: 10.1088/1755-1315/492/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions of fish meal with larvae meal black soldier fly (Hermetia illucens) on the performance of female quail

Abstract: BSF larvae meal contains protein which is very high so that it can be used as a protein source to replace fish meal. This study aims to determine how much the use of BSF larvae meal in substituting fish meal for consumption, weight gain and feed conversion in quails. This study used 200 7-day-old female quails that were kept for 6 weeks 42 days with an average initial weight of ± 23 grams. This study uses a completely randomized design (CRD), which consists of 4 treatments and 5 replications. Using experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
1
1
1
Order By: Relevance
“…Increased HILM inclusion levels in diets increase nutrient digestibility, promoting growth performance due to a decrease in non-starch polysaccharides. In contrast to our findings, Yusuf et al (2020) reported that female quails fed a diet with FM and SBM substituted with varying levels of HILM up to 10% showed no significant difference in weight gain or final live body weight. This could have been attributed to the nutrient profile of the control diet (0% HILM), which significantly had a higher proportion of methionine, calcium, and protein compared to the other experimental diets.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Increased HILM inclusion levels in diets increase nutrient digestibility, promoting growth performance due to a decrease in non-starch polysaccharides. In contrast to our findings, Yusuf et al (2020) reported that female quails fed a diet with FM and SBM substituted with varying levels of HILM up to 10% showed no significant difference in weight gain or final live body weight. This could have been attributed to the nutrient profile of the control diet (0% HILM), which significantly had a higher proportion of methionine, calcium, and protein compared to the other experimental diets.…”
Section: Discussioncontrasting
confidence: 99%
“…The incorporation of full-fat HILM in the diet increased the amount of crude fat content, which is consistent with previous studies of ISA Brown chicks and pullets by Sumbule et al (2021) . Similarly, feed formulated with HILM as an ingredient for female quail chicks as a substitute for FM ( Rastrineobola argentea ) exhibited a considerable increase in CP ( Yusuf et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A farinha de BSF ainda pode ser usada em substituição ao uso da farinha de peixe, em 100% de substituição (9,56% de farinha BSF) não influenciou negativamente parâmetros de peso do ovo, unidade haugh, índice de gema e cor da gema, já em níveis mais baixos, de 3,18% de farinha ou a 0% de inclusão, ocasionou em aumento da produção de ovos (Suparman et al, 2020). Yusuf et al (2020) reforça o achado anterior, indicando que a farinha de peixe pode ser substituída a 100% pela farinha de larvas BSF, sem causar prejuízos ao desempenho das codornas, como na conversão alimentar, consumo de ração e no ganho de peso. 2020) também traz conclusões quanto a substituição da farinha de peixe pela farinha de larvas BSF, 13,15% de farinha (100% de substituição) melhorou a produção e massa de ovos das codornas, enquanto o estado de saúde não se alterou, com base nas análises hematológicas feitas, já o estado imunológico melhorou, mostrando melhor atividade fagocitaria dos macrófagos e maior título de anticorpos para o vírus da gripe aviaria.…”
Section: Dípteraunclassified